IMPLEMENTATION OF LECTURE AND QUESTION AND METHODS ON THE EFFECTIVENESS OF ISLAMIC EDUCATION LEARNING IN INTEGRATED AL-ULUM ISLAMIC IN MEDAN - Febrian, Bintang; Anggraini, Dian Sri; Samin, Nur Mala; Sabila, Sabila; Yunan Harahap, Muhammad (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to explain the implementation of lecture and discussion methods in improving the learning outcomes of Islamic Religious Education (PAI) in Al-Ulum Integrated Islamic High School in Medan. The method used is qualitative, with data collection techniques through observation and interviews. Based on the research conducted, the researcher draws the conclusion that the lecture method applied in the learning process is a lecture method interspersed with question-and-answer methods. The discussion method used in this learning process is the small group discussion method. The learning outcomes of students in classes that apply the lecture method, in terms of cognitive aspects, have increased, and in terms of affective aspects, students can accept learning well. The results indicate that the use of lecture and question and answer methods is very necessary in the online learning process. The combination of lecture and question and answer methods needs to be applied to create interaction in the classroom. The implementation of gestures in teaching is very effective in engaging students who are in the concrete operational stage.